2022
DOI: 10.1038/s41598-022-06344-y
|View full text |Cite
|
Sign up to set email alerts
|

Transmutation of long-lived fission products in an advanced nuclear energy system

Abstract: Disposal of long-lived fission products (LLFPs) produced in reactors has been paid a lot attention for sustainable and clean nuclear energy. Although a few transmutation means have been proposed to address this issue, there are still scientific and/or engineering challenges to achieve efficient transmutation of LLFPs. In this study, we propose a novel concept of advanced nuclear energy system (ANES) for transmuting LLFPs efficiently without isotopic separation. The ANES comprises intense photoneutron source (P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The moderator could soften the neutron at the LLFPs assembly region while having little effect on the neutron energy spectrum of the entire core, as it is loaded in the radial blanket region with a small loading mass. The isotope abundances of these LLFPs nuclides are shown in Table 4 , and their chemical forms for assembly loading are explained in detail in our previous work 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderator could soften the neutron at the LLFPs assembly region while having little effect on the neutron energy spectrum of the entire core, as it is loaded in the radial blanket region with a small loading mass. The isotope abundances of these LLFPs nuclides are shown in Table 4 , and their chemical forms for assembly loading are explained in detail in our previous work 23 .…”
Section: Methodsmentioning
confidence: 99%
“…If an average of approximately 1 wt% MAs is loaded to the LFR core, a transmutation rate of 10% per year or more was foreseen without deterioration of the core characteristics 6 . For LLFPs, an advanced nuclear energy system driven by an intense photoneutron source has been proposed to transmute efficiently the LLFPs assembly composed of 79 Se, 93 Zr, 99 Tc, 107 Pd, 129 I, 135 Cs and 137 Cs 23 . It is shown that the 79 Se, 99 Tc, 107 Pd, 129 I and 137 Cs could be transmuted by more than 30% within 20 years and their effective half-lives can decrease drastically from ~ 10 6 to less than 10 2 years.…”
Section: Introductionmentioning
confidence: 99%